Soft, Biological and Composite Nanomaterials - Kim, Beom Soo; Gupta, Arvind (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The progress in the area of nanotechnology has opened the door for the fabrication of soft, biological, and composite nanomaterials for targeted applications. Nanomaterials are known to enhance the properties and functionality of composite materials several fold. The properties for the desired applications can often be achieved by the addition of small amounts of nanomaterials into soft materials such as polymers, gels, and biomaterials. This book condenses investigations by scientific groups from highly diverse research fields, which will be beneficial for the wider scientific community.